Redefining Banyumas Local Values: Symbolisms in Batik Motifs - Purwaningsih, Dyah Raina; Sholikhah, Ika Maratus; Wardani, Erna (Bina Nusantara University, 2018)
This research aimed to find the types of signs using Peircean semiotic theory namely icon, index, and symbol in Banyumas batik motifs. The researchers were going to describe the Banyumas local values depicted in each of the batik motifs. Moreover, Banyumas local values were reflected from the explained batik motifs. This research was a descriptive qualitative research by applying embedded-case study. The research was limited on Banyumas batik motifs which contained natural symbols; they were Jahe Rajang, Lumbon, Babon Angrem, Peksi Gowok, and Serayuan. There were two types of data to be analyzed, namely primary and secondary data. There were two key informants that the researchers met and interviewed to obtain more reliable data. To gain the primary data, the researchers conducted some series of interview with the first informant, a Banyumas batik artisan who was very dedicated to maintain the existence of batik tulis (hand-painted batik). Meanwhile, to gain the secondary data, the researchers visited a Banyumas culture activist. The results show that Banyumas batik motifs are made with certain purposes and meanings. Each of the motifs analyzed in this research carries important signs. It reflects the values and beliefs adhered by the local people. Through these motifs and the appreciation of batik, Banyumas local value like Cablaka (straightforward, honest, and genuine) reflects the index as one type of sign.